2005
DOI: 10.18267/j.pep.254
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of Current Account for Turkey: Intertemporal Solvency Approach

Abstract: Abstract:This paper examines sustainability of current account for Turkey during the period 1987:Q1 -2002:Q4. Using the usual intertemporal borrowing constraint, I have tested for a long-run relationship between Turkey exports and imports (measured in real terms to real gross domestic product) using quarterly data. In my empirical analysis of the sustainability of current account for Turkey, cointegration approaches have been used. Empirical results suggest that there exists a unique long-run or equilibrium re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 18 publications
4
13
0
3
Order By: Relevance
“…Using this approach Husted (1992), Bahmani-Oskooee and Rhee (1997), Fountas and Wu (1999), Arize (2002), Tang (2002), Baharumshah, et al (2003), Irandoust and Ericsson (2004), Keong,etal. (2004), Kalyoncu (2005), Narayan and Narayan (2005), Tang and Mohammad (2005), Hollauer and Mendonça (2006), Cunado, et al (2008), Erbaykal and Karaca (2008), Verma and Perera (2008), Kalyoncu and Ozturk (2010), Pattichis (2010), Greenidge, et al (2011) andHolmes, et al (2011) have reported mixed evidence across countries on the issue of the current account imbalance sustainability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using this approach Husted (1992), Bahmani-Oskooee and Rhee (1997), Fountas and Wu (1999), Arize (2002), Tang (2002), Baharumshah, et al (2003), Irandoust and Ericsson (2004), Keong,etal. (2004), Kalyoncu (2005), Narayan and Narayan (2005), Tang and Mohammad (2005), Hollauer and Mendonça (2006), Cunado, et al (2008), Erbaykal and Karaca (2008), Verma and Perera (2008), Kalyoncu and Ozturk (2010), Pattichis (2010), Greenidge, et al (2011) andHolmes, et al (2011) have reported mixed evidence across countries on the issue of the current account imbalance sustainability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Türkiye'de cari açığın optimal sürdürülebilirliğini inceleyen diğer çalışmalarla kıyaslandığında Selçuk (1997), Kalyoncu (2005) Diğer taraftan modelden elde edilen ampirik sonuçlar tüketicilerin, kriz dönemlerinde tampon görevi görerek tüketimlerini kısmasının daha fazla cari açığın oluşmasını önlediği, ancak ekonominin normal seyrinde sabırsız tüketicilerin gelecek tüketimlerini bugünden tüketime yönlendirmeleri diğer bir deyişle tüketim artışının yabancı ülkelerden borç alınarak gerçekleştirilmesi, 2001 sonrasında spekülatif sermaye girişlerinin ülkeye girmesinde etkili olmaktadır. Şekil 5 incelendiğinde 2001 krizi sonrası dönemde gerçekleşen cari denge serisinin dalgalı bir seyir izlemesi de bu durumu işaret etmektedir.…”
Section: Modelden Bulunan Gerçekleşen Cari Denge İle Optimal Cari Denunclassified
“…Policies that could be used to decrease the current account deficit and or improve the sustainability of the current account deficit have become major concerns of policy makers. Considering the importance of the current account deficit problem, Kalyoncu (2005), Ogus and Sohrabji (2008b), Peker (2009) and Binatli and Sohrabji (2012) have analyzed current account sustainability in Turkey for different periods and by employing different methods.…”
Section: Introductionmentioning
confidence: 99%